The impact of the use of concentrated solar energy in reducing environmental costs (Journal of Accounting and Financial Studies ( JAFS ), 2023)
The aim of this research is to highlight the importance of reducing the environmental costs associated with the production of electric energy using the concentrated solar energy system, to encourage the trend towards investment in clean energy, to raise the level of production efficiency of electric energy and to move away from investment in traditional stations to fill the shortfall in the electric power production company, where he showed This research is part of the knowledge foundations of environmental costs and the concentrated solar energy system, where the company's production of electric energy was calculated by collecting the productivity of the company's gas stations as well as the costs of operating and maintaining them in addition to the productivity for the year 2019, and the resulting emissions of these stations were calculated and estimated according to international methods and a statement of their impact on the cost per k w h .